Optimizing Food & Baverage Company Performance Through Governance and Social Responsibility: Random Effect Model Approach - Dwianto, Agus; A'yun , Annisa Qurrota; Kaira, Lamin; Sesay, Daniel Kassim; Turay, Ibrahim Rahman (Universitas Ahmad Dahlan, Yogyakarta, 2024)
The purpose of this study is to improve the efficiency of food and beverage companies listed on the Indonesia Stock Exchange by implementing GCG & CSR principles. Using panel data from 95 companies covering the period 2018-2022 and using the Random Effects model, the regression analysis shows that the Board of Commissioners has no statistically significant effect on company performance. In contrast, the Audit Committee shows a significant and beneficial impact. The novelty of this study emphasizes the complex nature of the interaction between GCG parameters, CSR, and business success in the food and beverage industry. Practical suggestions include increasing the authority of the Audit Committee to improve performance and applying CSR more contextually to reduce the impact of the Board of Commissioners. The contribution of this research is a valuable understanding of the interaction between governance dynamics and CSR in the context of strategic decision-making.